Glaucoma in Community: An Opportunistic Screening in Cataract Screening Programs - Rajbanshi, Lily (Birat Journal of Health Sciences, 2019)
Introduction: Glaucoma is an optic neuropathy for which elevated intraocular pressure is considered as major risk factor. Glaucoma is the second most common cause of blindness after cataract. Since visual loss in glaucoma is irreversible, management strategies must be focused upon early detection and prevention of disease progression through strict control of intraocular pressure.Objectives: To estimate the ocular morbidity of glaucoma in community screening camps and to estimate the types of glaucoma.Methodology: It is a Community based opportunistic screening program. Study was carried out at community screening camps for cataract from August 2009 to August 2010. Five hundred five patients equal and above 50 years were examined in five screening camps conducted in Kathmandu valley. Glaucoma suspects were identified on the basis of shallow anterior chamber, intraocular pressure > 20 mm of Hg, abnormal frequency doubling perimetry (FDP), cup to disc ratio (CDR) >0.7:1, asymmetric CDR > 0.2:1, unhealthy NRR and the other disc findings suggestive of glaucoma. Glaucoma suspects were re-examined in tertiary eye hospital (TIO) in order to make a final diagnosis and provide treatment.Result: Out of 505, 67 glaucoma suspects were re-examined in Tilganga Institute of Ophthalmology. Number of patient diagnosed glaucoma was 17 (3.37%). Of them 9 patients (1.78%) had POAG, 4 (0.79 %) had secondary glaucoma, 3 (0.59%) had normal tension glaucoma and 1 (0.20 %) had ocular hypertension.Conclusion: Morbidity of glaucoma is very high in community and more screenings in larger scales are needed in order to decrease the burden of blindness due to glaucoma.